A prognostic classification based on the International Association for the Study of Lung Cancer histologic grading and immunoscore in KRAS‐mutant invasive non‐mucinous adenocarcinoma. Issue 7 (4th March 2022) - Chi, Kaiwen; Sun, Wei; Yang, Xin; Wu, Jianghua; Wang, Haiyue; Liu, Xinying; Mao, Luning; Zhou, Lixin; Huang, Xiaozheng; Lin, Dongmei
Abstract: Background: Tumor immune cell infiltration is important in the prognosis of patients with lung adenocarcinoma. The aim of this study was to develop a prognostic classification based on the tumor immunoscore. Methods: Patients with KRAS ‐mutant invasive non‐mucinous lung adenocarcinoma who underwent radical surgery were enrolled in the study. Histologic grading was assessed according to the recommendations of the International Association for the Study of Lung Cancer. Programmed death‐ligand 1 (PD‐L1) and CD8 expression was detected using immunohistochemistry. The number of CD8 + tumor‐infiltrating lymphocytes (TILs) per high‐power field was assessed. A classification based on histological grade and CD8 + TIL level was established (Grading‐Immunoscore type): low‐to‐medium grade with high or low infiltration (type A); high‐grade, high‐infiltration (type B); and high‐grade, low‐infiltration (type C). Results: A total of 112 patients participated. In the multivariable analysis, histological grading and level of CD8 + TILs were independent prognostic factors for overall survival (OS) and progression‐free survival (PFS) ( p  < 0.001 and p  = 0.007, respectively). Patients with type A tumors had the best OS and PFS, whereas those with type C tumors had the worst OS (89.6%, 65.0%, and 29.5% 5‐year OS for types A, B, and C, respectively). PD‐L1 positivity and high expression rate was highest in type B tumors (tumor proportion score [TPS] ≥ 1%: 29.4%, 73.1%, and 42.9%; TPS ≥50%: 7.8%, 42.3%, and 17.1%, for types A, B, and C, respectively). Conclusions: The Grading‐Immunoscore classification refines the prognostic grouping of histological grading and might aid in the screening of potential candidates for immunotherapy in patients with KRAS ‐mutant adenocarcinoma. Abstract : The Grading‐Immunoscore classification refines the prognostic grouping of histological grading and might aid in the screening of potential candidates for immunotherapy in patients with KRAS ‐mutant adenocarcinoma.